A Case of Tracheobronchopathia Osteochondroplastica Diagnosed by Fiberoptic Bronchoscopy Upon Removal of an Aspirated Crown. Issue 2 (2001) - Matsuba, T.; Komori, M.; Matsunaga, R.; Andoh, K.; Hirota, N.; Hara, N.
Abstract : Tracheobronchopathia osteochondroplastica (TO) is a relatively rare benign disease, around 300 and 130 cases have been reported in English and Japanese literature, respectively. Most of the cases have been diagnosed incidentally at autopsy. Due to the widespread use of fiberoptic bronchoscopy (FOB), the number of cases diagnosed upon examination is increasing. Here, we report a case of a 72 year-old man with a history of crown aspiration, who was diagnosed as TO upon removal of a foreign body using FOB. The diagnosis of TO and the removal of an aspirated crown by FOB are discussed.